Extraction and Characterization of Starches from the Pulp and Peel of Native Plantain (Musa AAB Simmonds) from Two Colombian Departments - Juan Pablo Castañeda-Niño; José Herminsul Mina-Hernández; José Fernando Solanilla-Duque (Polysaccharides)
Plantain (Musa AAB Simmonds) of the Dominico hartón variety from two Colombian territories (Cauca and Risaralda) with differences in altitude was used to extract the flour and starch from the pulp and peel. The plantain of Cauca origin presented the highest yield in flour extraction. Starch extraction was based on the use of an aqueous solution of sodium metabisulfite, achieving the highest yield in starch extraction (above 80% d.b.) when using a concentration of 1.2% of sodium metabisulfite, highlighting the best performance in the plantain of Risaralda origin. In the characterization of the starches, the granules from the pulp showed a larger size, higher amylose content, lower ash content, lower water absorption and solubility capacity, higher melting enthalpy, and higher crystallinity than those obtained with the starches from the banana peel. The starch from Cauca pulp presented properties characteristic of a structure with higher hardness.